Acupuncture treatment preserves soleus muscle mass and improves mitochondrial function in a rat model of disuse atrophy - Sarah Mockler; Yun-Ju Fang; U-Ter Aondo Jia; Jinho Park; Joo Hyun Kim; Yoonjung Park; Adam J. Chicco; Masataka Umeda; Sukho Lee; Eunhee Chung (Integrative Medicine Research, 2025)
Background: Muscle atrophy leads to debilitating loss of physical capacity, particularly when alternative treatments are needed. Acupuncture is proposed as a potential therapy for disuse atrophy, but its effects on muscle biology remain unclear. This study evaluated the effects of acupuncture on soleus muscle mass and mitochondrial function in a rat model of immobilization-induced atrophy. Methods: Female Sprague Dawley rats were assigned to three groups: Control (CON), casting-induced immobilization (CT), and CT with acupuncture (CT-A) (n = 8). Immobilization of the left hindlimb lasted for 14 days, and acupuncture was performed at specific acupoints (stomach-36, gallbladder-34) three times per week for 15 min. Mitochondrial function was assessed in saponin-permeabilized fibers, and signaling molecules regulating muscle mass were analyzed by Western blot. Results: CT-A attenuated soleus muscle atrophy compared to CT. Under fatty acid substrate conditions, CT reduced complex I and II-supported oxidative phosphorylation (OXPHOS) compared to CON, while CT-A decreased respiratory leak and enhanced OXPHOS coupling relative to CT. Without fatty acids, CT-A decreased both respiratory leak and complex I and II-supported OXPHOS compared to CON, but differences between CT and CT-A were not significant. AMPKα activity (p-AMPKα/AMPKα) was significantly elevated in the CT group compared to the CON group, but returned to CON levels in the CT-A group. However, there were no changes in proteins associated with muscle atrophy or autophagy markers among the groups. Conclusion: Acupuncture mitigates immobilization-induced muscle atrophy and preserves mitochondrial function, suggesting its potential as a therapeutic approach for muscle disuse conditions.